The role of ownership structure and board characteristics in stock market liquidity - Wajih Abbassi; Ahmed Imran Hunjra; Suha Mahmoud Alawi; Rashid Mehmood (International Journal of Financial Studies, 2021)
Corporate governance plays a significant role in the value of shareholders and share prices, hence stock market liquidity is affected. Previous research has mainly focused on the issue in developed markets, whereas in developing countries there is a need to analyze the influence of corporate governance on stock market liquidity. Therefore, the present study aims to examine the impact of ownership structure and board characteristics on stock market liquidity of non-financial firms of South Asian countries such as Pakistan, Sri Lanka, Bangladesh, and India. The data in the study is collected from the DataStream for the 2011-2020 period. The study uses a fixed effect model for the analysis of the data and hypotheses testing and generalized method of moments (GMM) is used to check the robustness of the results. The findings of the study indicate that institutional ownership, board size, board independence, and CEO duality have a significant and positive impact on stock market liquidity, whereas managerial ownership has a significant and negative effect on stock market liquidity.
Keywords: 330; board of directors; institutional ownership; managerial ownership; stock market liquidity